FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI BANTUAN MODAL TERNAK SAPI PADA RUMAHTANGGA PETERNAK SAPI POTONG DI KECAMATAN TOMPASO BARAT - Manopo, Keine A; Umboh, S J.K; Waleleng, P O.V; Elly, F H (Universitas Sam Ratulangi, 2019)
FACTORS AFFECTING THE ALLOCATION OF CAPITAL ASSISTANCE IN HOUSEHOLD CATTLE BREEDER IN DISTRICT WEST TOMPASO. The purpose of this research is to analyze the factors that are influencing farmer households’ decision making in allocating financial assistance for livestock production in West Tompaso sub-district, Minahasa regency. This research applies surveying method among 30 household samples. Data collecting was done in October until November 2018. Data analysis is proceeded by using simultaneous equation analysis. The result of this research shows that financial assistance allocation for cattle business is 39,76% and the rest 60,24% is the allocation for any farming businesses other than cattle business. The financial assistance for cattle business is significantly influenced by the amount of financial assistance given, feeder cattle value and the allocation of financial assistance for farming businesses other than cattle business. Meanwhile, the allocation of financial assistance for farming businesses other than cattle business is significantly influenced by the amount of financial assistance received and the allocation of the financial assistance for cattle business.Keywords: Allocation, Financial Assistance, Beef Cattle.